Aeolian deposits of the humid tropics: case of the marine-coastal strip of the eastern part of the Azuero Peninsula, Panama. - Rivera-Solís, Jaime Alberto (2021)
The purpose of the investigation was to demonstrate the incidence of wind as a morphogenetic agent through the correlation of the sand clasts that constitute the marine-coastal geofacies.  Morphoclimatic limit theory was selected and the data on temperature, precipitation and winds compiled; field activities included the classification of the geoforms of accumulation and erosion as well as the sampling of sands per geofacies.  Sand samples (453 g) were sieved to separate their components and assay clast sizes, followed by stereomicroscopic examination to determine roundness and sphericity by visual comparison.  Subsequently, the sample from the coastal plain (1 g) was treated with 1N potassium dichromate solution (K2Cr2O7) and sulfuric acid (H2SO4), to oxidize and eliminate organic matter and determine its genesis.  Finally, the correlation between mesolittoral sand as independent variable and origin of aeolian deposits per geofacies was found to be of positive linear nature with high correlation coefficients (ρ) for coastal dunes (ρ ± 0.98), nebka dunes (ρ ± 0.98) and sand mantles (ρ ± 0.96).